Application of Alvarado scoring system in the diagnosis of acute appendicitis. - Hindosh, Laith. Naif.; Kamal, . Zuhair Bashir; Alnasir, . Mumtaz khider; Hussein, Wisam Abdulateef (AL-Kindy College Medical Journal, 2015)
Background: Acute appendicitis is the most common abdominal surgical emergency. The diagnosis of this condition is still essentially clinical and there is difficulty in the clinical diagnosis, especially among elderly, children and patients with a typical presentation, so early and accurate diagnosis of acute appendicitis is important to avoid its complications.Objectives: To evaluate the degree of accuracy of Alvarado scoring system in the diagnosis of acute appendicitis.Method: Two hundred patients were admitted to the Alkindy Teaching Hospital from January 2011 to april 2014- presented with symptoms and signs suggestive of acute appendicitis. After examination and investigations all patients were given a score according to Alvarado scoring 10 (8 variables) and they were classified accordingly to 6 groups of scores (score 5, score 6, score 7, score 8, score 9 and score 10). All the patients underwent appendectomy and the appendix specimens were sent for histopathological examination and the patients were divided into two groups:1-patients 7 score (164 patients)2-patients